Interpreter-mediated police interviews resource] : a discourse-pragmatic approach - Nakane, Ikuko; SpringerLink (Online service). (London : Palgrave Macmillan, 2014)
This book shows how participation of interpreters as mediators changes the dynamics of police interviews, particularly with regard to power struggles and competing versions of events. The analysis of interaction offers insights into language in the legal process.
Keywords: Linguistics; Sociolinguistics; Translation and interpretation; Law; Criminal law; Criminology; Communication; Criminological Theory; Law, general; Translation; Criminal Law; Communication Studies